1985
DOI: 10.1093/infdis/151.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immunity Induced by Naturally Acquired Rotavirus and Norwalk Virus Infection on Two Remote Panamanian Islands

Abstract: For better understanding of the role of humoral immunity in ameliorating infections with rotavirus (RV) and Norwalk virus (NW), 305 Cuna Indians living on two isolated islands located off Panama's Carribean coast were surveyed daily for diarrhea over a seven-month period. Nine (8%) of 108 persons with a baseline RV antibody titer of greater than 1:4 developed RV infection compared with 70 (46%) of 151 persons with a baseline RV antibody titer of less than 1:4 (P less than .001). Thirty-eight (25%) of 151 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 14 publications
4
29
1
Order By: Relevance
“…This result is consistent with the finding in the volunteer studies and outbreak investigations, in which short-term (6-14 weeks) protective immunity was demonstrated against homologous NVs [Dolin et al, 1972;Wyatt et al, 1974] and the presence of serum antibody correlated with resistance to NV infection [Black et al, 1982;Nakata et al, 1985;Ryder et al, 1985]. However, controversies about the antibody protection against NVs have also been reported.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with the finding in the volunteer studies and outbreak investigations, in which short-term (6-14 weeks) protective immunity was demonstrated against homologous NVs [Dolin et al, 1972;Wyatt et al, 1974] and the presence of serum antibody correlated with resistance to NV infection [Black et al, 1982;Nakata et al, 1985;Ryder et al, 1985]. However, controversies about the antibody protection against NVs have also been reported.…”
Section: Discussionsupporting
confidence: 91%
“…The overall IDR of 0.7 NLV seroconversions per child-year in children less than 4 years of age that we observed is similar to that reported by Ryder et al (1985) in young children in rural Panama (0.63) but is higher than the NLV seroincidence rates reported by three other longitudinal studies of NLV infection in children in Canada (<0.001-0.19), Finland (0.27) and rural Bangladesh (0.29) [Gurwith et al, 1983;Lew et al, 1994;Black et al, 1982]. Yet, our estimate of NLV seroincidence is likely to be an underestimate of the total burden of human calicivirus infection in this study population.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have reported that a high percentage of children in developing countries have antibodies to NLVs [Greenberg et al, 1979;Echeverria et al, 1983;Ryder et al, 1985;Cukor et al, 1980;Black et al, 1982;Gabbay et al, 1994;Jiang et al, 1995b], and four studies have examined NLV seroincidence in young children in rural Bangladesh, rural Panama, Canada, and Finland [Black et al, 1982;Ryder et al, 1985;Gurwith et al, 1983;Lew et al, 1994], but the impact of NLV infection on child health is still largely unknown. This study reports an association between NLV seroconversion and vomiting in young children and evaluates NLV seroincidence among urban children in a developing country.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of exposure to these viruses were similar to that reported for Kuwaitis (98% and 96%, respectively) and for foreign workers in Kuwait (98% and 95%, respectively) [Dimitrov et al, 1997]. Antibodies against NV, which has been examined more extensively, were also high in Panama [98%, Ryder et al, 1985], Indonesia, Papua New Guinea [90% and 100%, Numata et al, 1994], and Australian aborigines [94%, Parker et al, 1994].…”
Section: Resultssupporting
confidence: 77%